Comparison of Identities Framed by News Sources and Media in Selected Chinese Newspaper Coverage on an Education Issues in Malaysia - Chang, Peng Kee; Ho Nee, Yong (2010)
The Chinese community in Malaysia is recognised as having a strong identity for its well preserved mother-tongue education. The development of Chinese education has experienced hardship for almost two centuries. The usage of Mandarin language as the medium of instruction for Chinese education since the early 20th century has no doubt been a unifying factor among the Malaysian Chinese community. In constructing the ethnic identity, Chinese education together with the Chinese newspapers and Chinese guilds are considered to be the three treasures（三宝）till today. The development of Chinese education has never been smooth sailing and the case of the policy change in the teaching and learning of mathematics and science subjects in English implemented in 2003 was a clear manifestation. The local Chinese newspapers had widely covered this issue when it was first announced in May 2002. This empirical research paper therefore attempts to compare some significant identities being framed in selected Chinese newspapers on this contemporary issue.